Towards an employer brand - An evidence-based approach to develop an employer brand: A case study of a Berlin-based business incubator in the online and mobile gaming industry - Ingo Fischer; Julia Kieler (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2015)
This paper analyses and lays the ground for the development of an employer brand that is designed to help a Berlin-based business incubator to attract and retain tech talent. The company case exemplifies which elements are necessary to develop an employer brand and how distinguishing characteristics of an employer brand may look like. It gets clear that an one-size-fits-all approach is not effective. – – Diese Studie analysiert und konzipiert die Entwicklung einer Arbeitgebermarke als Instrument zur Rekrutierung und Bindung von Softwareentwicklern für einen Berliner Inkubator in der Online- und Mobile-Gaming Branche. Die Studie macht anhand eines Praxisfalls deutlich, welche Elemente benötigt werden, um zu einer Arbeitgebermarke zu gelangen, wie diese Elemente evidenzbasiert entwickelt werden können und welche differenzierenden Kernelemente eine Arbeitgebermarke umfassen kann. Es wird deutlich, dass eine One-size-fits-all Lösung nicht zielführend wäre.
Keywords: 650; Personalmarketing; Personalbeschaffung; Mitarbeiterbindung; IT-Berufe; Computerspieleindustrie; Technologiepark; Berlin; Deutschland